Europeidad y medios: identidad nacional y esfera pública - Philip R. Schlesinger (Estudios sobre las Culturas Contemporáneas)
This paper sets out some of the key issues concerning relations bet\ veen the mass media and the nation-state in the context of dynamic and uneven processes of Europ>earusation. European political developments are throwing up new questions about communication. In the post- Cold War period, the framing of European space as divided in two by opposed blocs has ceased. The European Union has become the dynamic point of attachment for most of the states of the continent and its federal potential means that how Europeans think about an overarching politic public space will probably have to change some time in the future.